Skerki Bank (Strait of Sicily) is a hotspot of molluscan biodiversity: multiple new records for Tunisian waters and description of three new species - Antit, Mouna; Gofas, Serge; Taviani, Marco (Frontiers in Marine Science, 2024)
Seabottom sampling of the Skerki Bank in the Strait of Sicily, updates the census of marine molluscs inhabiting a biogeographically key sector of the Mediterranean basin. One single dredge haul at 112 m depth yielded 110 molluscan species belonging to Gastropodas, Bivalvia and Scaphopoda, of which 41 are new records for Tunisian jurisdictional waters, including three gastropod species new to science. Nearly all the species are shared with the fauna inhabiting the adjacent Italian waters, and most of them are reported also from Malta. We stress that sites characterized by a relevant species richness, diagnosed by hosting more than 100 species, inclusive of rare taxa, are important areas for conservation in need of adequate management.